If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 1) + 21 = 0 Reorder the terms: 2(1 + x) + 21 = 0 (1 * 2 + x * 2) + 21 = 0 (2 + 2x) + 21 = 0 Reorder the terms: 2 + 21 + 2x = 0 Combine like terms: 2 + 21 = 23 23 + 2x = 0 Solving 23 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + 2x = 0 + -23 Combine like terms: 23 + -23 = 0 0 + 2x = 0 + -23 2x = 0 + -23 Combine like terms: 0 + -23 = -23 2x = -23 Divide each side by '2'. x = -11.5 Simplifying x = -11.5
| 4(x+3)+16= | | 6+3p+45=-38 | | 3p+35=2 | | 4y+2/5=4-3y/6 | | 4y+2/5 | | 2(x+7)=9-2x | | 2(x+3)=4(2x-7) | | 2sin^2x+5sin^2x=3 | | 4x+12n=36 | | Ax+ca=b | | 4x+3(x+2)=13 | | xa+cx=b | | ax+xc=b | | xa+xc=b | | 4y-8=1+5y-36 | | Ax+cx=b | | 2.8=(x/5)^3 | | 43x=4x+18 | | 6x+3=7+4x | | x+4=225 | | 6*(4x-3)+20x-24x^2=14 | | x+6=258 | | 5x-4=5x+4 | | 2=3 xx1 | | ax+3=c | | 3x+5y=200.4 | | 4-3a+4=0 | | 7x-3(x+2)=4x+3 | | 2(x+5)=4x-(2x-10) | | 6x(4x-3)+20x-24x^2=14 | | 6(2-3x)=5(x+4) | | (a-b)(2a^3-ab+3b^2)=0 |